Water Contamination by Heavy Metals and their Toxic Effect - Lama, Sumaya Assanousi Eshtiwi (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Water pollution by heavy metals is a serious problem affecting humans and animals. Heavy metal ions can cause health problems such as liver and kidney damage, skin diseases, mental retardation and cancer. To avoid the harmful effects of these toxic metals, it is important to find an environmentally friendly and cost-effective way to remove heavy metal ion pollution from diseases. Biosorption is an environmentally friendly process based on plant biomass.Algae and agricultural waste and microorganisms. This method is environmentally friendly and does not require much investment. This review provides basic knowledge on heavy metal pollution research and environmental removal.